Avaliação da qualidade da assistência em saúde bucal para prevenção e tratamento da mucosite oral em pacientes submetidos ao transplante de células-tronco hematopoiéticas - Marinho, Liliane Cristina Nogueira (2020)
Introduction: Oral mucositis (OM) is an inflammation of the oral mucosa, quite prevalent in patients undergoing Hematopoietic Stem Cell Transplantation (HSCT), contributing to the interruption of antineoplastic treatment. Photobiomodulation therapy (PBM) has been proposed due to its preventive and therapeutic action for OM. Objective: To evaluate the quality of oral health care through the process and result in the prevention and treatment of OM in patients undergoing HSCT. Materials and methods: Observational, descriptive, prospective and health quality assessment study, appropriate according to Squire 2.0. The sample consisted of thirty-six patients who received previous dental treatment and PBM as a preventive protocol for oral mucositis. When diagnosed with mucositis, patients received therapeutic PBM. The patients were followed up and evaluated during the conditioning regime (T0), one day after HSCT (T1), with 5 days after HSCT (T2) and with 10 days after HSCT (T3). The following indicators were used to evaluate the process: Evidence-based therapy, Assessment and recording of symptoms at all visits, Preventive care with PBM during hospitalization and Therapeutic plan for the outbreak of symptoms and worsening. The result indicators were expressed in percentages, being the Percentage of individuals who developed: OM; OM according to gravity; Ache; Severe, mild and / or moderate pain; Oral changes; OM according to sex; OM in leukopenic individuals. Plus percentage of individuals who used painkillers during therapy; Pain reduction; Presence of another associated treatment; Individuals with comorbidities who developed OM and Individuals with autologous and allogeneic transplants who developed OM. Descriptive and statistical analysis of the indicators was performed using the non-parametric Wilcoxon test and the Chisquare test with a significance level of 5%. Results: For the process, it was observed that in all indicators, 100% of the sample obtained assistance within the desirable standard. Result indicators showed that 66.6% of patients had Oral Mucositis in at least one follow-up period, with a statistically significant increase between times T1 and T2, as well as between times T1 and T3 (p <0.05), with a predominance grade I (p = 0.014). Four patients (16.7%) reported pain, both at T2 and T3, with a statistically significant increase between T1 and T2 (p <0.05), with moderate pain being the most observed, with no reports of severe pain. In the evaluation of the leukocyte count, it can be observed that in the period in which the patients had a greater number of oral mucositis (T2 and T3), they exhibited leukopenia, but without statistically significant differences (p> 0.05). OM had no statistically significant association with pain, associated treatment, leukopenia, comorbidities and the type of transplant, presenting for females (p = 0.015). There was no statistically significant association for pain reduction. Conclusion: The results presented showed excellent process indicators used to assess the quality of health service provision. The results of the photobiomodulation protocols demonstrated that although there is still the development of OM in these patients, there was a predominance of grade I, with less severity of OM as well as associated pain.